2022
DOI: 10.1021/acsaelm.1c01095
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Textile Manufacturing Methods for Fabricating Triboelectric Nanogenerators with Balanced Electrical and Wearable Properties

Abstract: Triboelectric nanogenerators (TENGs) are foreseen as a leading candidate to harvest mechanical energy from ambient sources such as human body movements. However, wearable TENGs, which are used for this purpose, require adequate wearability for long durations, in addition to sufficient electrical outputs. So far, it has been difficult to achieve this through the predominantly plastic-based wearable TENGs constructed using conventional nanogenerator fabrication methods. This Article evaluates the use of textile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…It was observed that yarn-coated TENG outperforms other TENGs (i.e., screen printed and dip-coated fabric made of the same conductive yarn) in output due to higher triboelectric contact surface area. The electrical output of the yarncoated TENG (i.e., open circuit voltage (V OC ) ~34.5 V, short circuit current (I SC ) ~60 nA, short circuit charge (Q SC ) ~12 nC) was superior to that of other TENGs (screen printed; V OC ~17.3 V, I SC ~43 nA, Q SC ~5 nC and dip-coated; V OC ~4.9 V, I SC ~11 nA, Q SC ~2 nC) and showed better cyclic stability up to 3000 contact separation cycles [155]. Xiao et al developed cotton yarn-based sweat-activated batteries (CYSAB) by drop coating black carbon (cathode, 4 cm), a bare portion (salt bridge, 0.5 cm), and subsequently wrapped with Zn foil (anode, 1.0 cm) of the same pristine cotton yarn.…”
Section: Yarn Shaped Durable E-textilesmentioning
confidence: 92%
“…It was observed that yarn-coated TENG outperforms other TENGs (i.e., screen printed and dip-coated fabric made of the same conductive yarn) in output due to higher triboelectric contact surface area. The electrical output of the yarncoated TENG (i.e., open circuit voltage (V OC ) ~34.5 V, short circuit current (I SC ) ~60 nA, short circuit charge (Q SC ) ~12 nC) was superior to that of other TENGs (screen printed; V OC ~17.3 V, I SC ~43 nA, Q SC ~5 nC and dip-coated; V OC ~4.9 V, I SC ~11 nA, Q SC ~2 nC) and showed better cyclic stability up to 3000 contact separation cycles [155]. Xiao et al developed cotton yarn-based sweat-activated batteries (CYSAB) by drop coating black carbon (cathode, 4 cm), a bare portion (salt bridge, 0.5 cm), and subsequently wrapped with Zn foil (anode, 1.0 cm) of the same pristine cotton yarn.…”
Section: Yarn Shaped Durable E-textilesmentioning
confidence: 92%
“…Reproduced with permission. [ 134 ] Copyright 2022, American Chemical Society. e) Method of conductive PA yarn and NPTY fabrication.…”
Section: Wearable Triboelectric Nanogeneratorsmentioning
confidence: 99%
“…(Figure 7d). [ 134 ] Here, three samples were fabricated using common textile manufacturing methods. One of them was fabricated using the yarn coating technique by applying a PDMS coating to a silver‐coated yarn and then knitting a 1 × 1 rib fabric.…”
Section: Wearable Triboelectric Nanogeneratorsmentioning
confidence: 99%
See 2 more Smart Citations